The Incentive Compatibility Condition, Firm Culture, and Social Norms under Moral Hazard: Theory and Evidence - Sanjit Dhami; Mengxing Wei (CESifo GmbH, 2024)
In a principal-agent model under moral hazard we examine the psychological and social motivations of the agent that influence the incentive compatibility condition (ICC) of the agent. Under “firm culture” firms emphasize that high effort is consistent with its culture. Under “industry-wide social norms” external to the firm, the social group emphasizes high effort levels. We only consider the case where the ICC is violated in the classical case. A significant fraction of the agents choose high effort. Firm culture backed by simple disapproval of low effort is more effective relative to our baseline under fixed wages. Strong social norms are as effective as firm culture under variable wages, but more effective under fixed wages. Firm culture dominates weak social norms. Variable wages induce high effort (incentive effects) but also crowd out intrinsic motivation in the form of (i) guilt aversion from not following firm culture and (ii) shame aversion from not following social norms.
Keywords: D01; D91; 330; incentive compatibility; insurance and incentives; firm culture; guilt-aversion; social norms; shame-aversion